Milk consumption and growth efficiency in Antarctic fur seal (Arctocephalus gazella) pups - John Arnould; IL Boyd; DG Socha (1996)
The body composition, milk consumption, and growth efficiency of Antarctic fur seal (Arctocephalus gazella) pups were measured over three consecutive lactation periods (1990-1992) at Bird Island, South Georgia. The body composition of pups differed between the sexes; whereas for any given age females were lighter than males, they had proportionately higher body lipid reserves than males. Milk consumption was determined on 388 occasions in 177 pups. Mean estimates of milk consumption ranged from 2.5 to 3.2 kg (42-53 MJ) during the 6-day perinatal period and from 2.9 to 3.6 kg (49-68 MJ) during the 1- to 2-day maternal attendance periods (feeding bouts). There were no differences in milk consumption between the sexes in any year. Both per-bout and per-day milk consumption increased steadily with age before decreasing significantly in the last 30-40 days of lactation. Per-bout milk consumption was positively related to the duration of the maternal foraging trip and attendance cycle, and both per-bout and per-day milk consumption were related to pup mass. Pups of both sexes consume the same amount of milk, but males direct more of their milk consumption into lean tissue growth than females, which accumulate greater adipose stores. Therefore, mass and mass changes may not be appropriate parameters for investigating differential maternal investment between the sexes in otariid pups.